Age and Sex Dependent Regulation of the Factor IX Gene in Mice - Kurachi, Sumiko; Hitomi, Eri; Kurachi, Kotoku (Thrombosis and Haemostasis, 1996)
Plasma factor IX and liver factor IX mRNA levels in two normal mouse strains (B6D2F1 and BALB/CJNIA) were determined in relation to aging and sex of the animals. With male B6D2F1 mice, mean plasma factor IX activity levels for the 14 and 21-22 month-old animals were found to be 124% and 226%, respectively, of the 5 month-old group. Similarly, liver factor IX mRNA levels for the same age animal groups were 145% and 227%, respectively, of the reference group. Mean plasma factor IX levels for the same age female animals were 132% and 175%, respectively, and were accompanied by similarly elevated liver factor IX mRNA levels, 119 and 175%, respectively, of the 5 month-old female group. Factor IX activity and mRNA levels for the 5,14 and 21-22 month-old female animal groups were lower than those of the corresponding male age groups by 25, 20 and 37%, and 20,36 and 38%, respectively. With BALB/CJNIA mice, similar correlation was observed between the advancing age and substantial elevations in the factor IX mRNA level as well as on the unequal factor IX mRNA levels in females and males.These results indicate that the plasma factor IX level in both male and female mice is greatly elevated with aging, in general agreement with a similar phenomenon observed for human populations, and that this increase is due to a similar elevation in the factor IX mRNA level in the liver. In mice, both factor IX activity and mRNA levels are significantly higher in males than in females, which has not been described for humans.